Syair Tionghua peranakan Indonesia - Low Kok On (2003)
Peranakan Chinese is considered a unique ethnich group in Indonesia due to assimilation of Malay culture into theirs. They used bahasa Baba which is sometimes called Melayu Baba in their daily conversation as well as in writing. It is through it that the Peranakan Chinese has produced amazingly a great deal of traditional poems, namely the pantun and syair. This report deals with the identity and beauty of Peranakan Chinese syair published in the 19th century.